2021
DOI: 10.1186/s12976-021-00145-y
|View full text |Cite
|
Sign up to set email alerts
|

Markov modelling of viral load adjusting for CD4 orthogonal variable and multivariate conditional autoregressive mapping of the HIV immunological outcomes among ART patients in Zimbabwe

Abstract: Background This study aimed to jointly model HIV disease progression patterns based on viral load (VL) among adult ART patients adjusting for the time-varying “incremental transients states” variable, and the CD4 cell counts orthogonal variable in a single 5-stage time-homogenous multistate Markov model. We further jointly mapped the relative risks of HIV disease progression outcomes (detectable VL (VL ≥ 50copies/uL) and immune deterioration (CD4 < 350cells/uL) at the last observed visit) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This resulted in a high influx of HIV patients in the HIV prevention programme. Studies have shown that patients who start ART with a higher CD4 cell count are generally well which can trigger non-adherence or low-risk perception to long-term therapy; hence, become LTFU [ 8 , 18 , 19 ]. The country also introduced HIV strategies like “test and treat all” which targeted the high-risk groups such as those with tuberculosis co-infection and serodiscordant partners, and pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a high influx of HIV patients in the HIV prevention programme. Studies have shown that patients who start ART with a higher CD4 cell count are generally well which can trigger non-adherence or low-risk perception to long-term therapy; hence, become LTFU [ 8 , 18 , 19 ]. The country also introduced HIV strategies like “test and treat all” which targeted the high-risk groups such as those with tuberculosis co-infection and serodiscordant partners, and pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible parameter MSM is employed for semi-Markov model analysis, enabling the selection of parameter distribution types such as Weibull, exponential, Gompertz, gamma, log-logistic, log-normal, generalized gamma (gengamma), original generalized gamma (gengama.orig), generalized F (genf), and original generalized F (genf.orig). To fit and optimize the parameter distribution, the Akaike information criterion (AIC) (15) was utilized to screen the data distribution parameters of the regression model. Subsequently, the distribution with the lowest AIC value was chosen to establish the parameter regression model.…”
Section: Data Distribution Selectionmentioning
confidence: 99%
“…According to the assumption of the Markov MSM, future transitions are only influenced by the current state, not by previous history; in other words, there is no aftereffect. However, in some diseases' actual development, it is unrealistic to adhere to the Markov hypothesis (14,15). For example, the occurrence of NI is related to the LOS, with longer stays increasing the infection risk (19).…”
Section: Discusscionmentioning
confidence: 99%
“…Nonetheless, viral rebound is now increasingly reported among people who had prior history of viral suppression. A study in Zimbabwe reported that the rates of rebound are higher than viral suppression [ 17 ]. However, there is paucity of data on viral rebound and the risk for rebound in most LMIC such as Tanzania.…”
Section: Introductionmentioning
confidence: 99%